Visual and Verbal Communication in the Music Video Clip Entitled “Millionaires” - Yoseph Anggara Putra Meta, Lau; Isnu Maharani, Sang Ayu; Rajeg, I Made (Udayana Journal of Social Sciences and Humanities, 2021)
This study is aimed at analyzing the elements of visual and verbal communication and the messages of the song lyrics of millionaires . The data of this study collected intensively through watching the music video clip and note-taking. In analyzing the data this study uses the main theory of principle visual communication elements by Dyer (1993), theory of sign by Goodwin (1992), and theory of meaning proposed by Leech (1974). The findings showed that the use of visuals was found 13 elements are appearance, manner, activity, props, and setting, visual or images. As for verbal communication elements, the finding showed 4 meanings representation: conceptual meaning, connotative meaning, affective meaning, and thematic meaning. Furthermore, there is a correlation between visual signs and verbal representation in the video clip as well as the meaning of the song lyrics.